The microbial changes in subgingival plaques of orthodontic patients: a systematic review and meta-analysis of clinical trials - Runzhi Guo; Yifan Lin; Yunfei Zheng; Weiran Li (BMC Oral Health, 2017)
Abstract Background Orthodontic treatment was found to have an impact on the quantity and constitution of subgingival microbiota. However, contradictory findings regarding the effects of fixed appliances on microbial changes were reported. The aim of this systematic review was to investigate the microbial changes in subgingival plaques of orthodontic patients. Methods The PubMed, Cochrane Library, and EMBASE databases were searched up to November 20, 2016. Longitudinal studies observing microbial changes in subgingival plaques at different time points of orthodontic treatment are included. The methodological quality of the included studies was assessed by Methodological index for non-randomized studies (MINORS). The studies that reported the frequency of subgingival periodontopathogens were used for quantitative analysis. Other studies were analysed qualitatively to describe the microbial changes during orthodontic treatment. Results Thirteen studies were selected, including two controlled clinical trials, three cohort studies and eight self-controlled studies. Four periodontopathogens, including Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi) and Tannerella forsythia (Tf), were analysed. Following orthodontic appliance placement, the frequencies of Pg and Aa showed no significant change (P = 0.97 and P = 0.77), whereas the frequency of Tf significantly increased (P < 0.01) during short-term observation (0–3 months). The frequency of Pi showed a tooth-specific difference, as it presented no significant difference (P = 0.25) at the site of the first molar but was significantly increased (P = 0.01) at the incisor. During long-term observation (> = 6 months), two studies reported that the levels of subgingival periodontopathogens exhibited a transient increase but decreased to the pretreatment levels afterwards. After removal of the orthodontic appliance, the four periodontopathogens showed no significant difference compared with before removal. Conclusion The levels of subgingival pathogens presented temporary increases after orthodontic appliance placement, and appeared to return to pretreatment levels several months later. This indicates that orthodontic treatment might not permanently induce periodontal disease by affecting the level of subgingival periodontal pathogen levels. Further studies of high methodological quality are required to provide more reliable evidence regarding this issue.